Influence of crown exposure on the morphological needle traits of nine conifers (Journal of Forestry, 2023)
The aim of this research was to investigate if the crown exposure of some conifers influenced to needle properties. The leaf morphological traits of sixty-six trees of nine conifers: Atlas cedar, Austrian pine, Blue spruce, Douglas fir, European spruce, European yew, Serbian spruce, Silver fir, and White fir, from six Belgrade parks, were analyzed. Five needles were measured from each of the four main crown exposures. Length, width, area and perimeter of needles were investigated. Species, parks in which they were found, as well as crown exposures, differed mostly in needle length and needle width. Correlations between measured needle traits were determined by linear regression analysis. Strong positive correlations were found between the length, perimeter, and area of needles. The differences among the species in terms of light requirement determine species for individual planting as light-loving or partial shade species (Atlas cedar, European spruce, Serbian spruce, Blue spruce, Austrian pine and Douglas fir), or for group planting as shade-loving species (Silver fir, White fir and European yew).